Strategic interaction in local fiscal policy : evidence from Portuguese Municipalities - Silva, Hélia (2011)
This paper aims at testing the degree of interaction between Portuguese municipalities’ expenditure levels by estimating a dynamic panel model, based on jurisdictional reaction functions. The analysis is performed for all 278 Portuguese mainland municipalities from 1986 to 2006, using alternative ways to measure neighbourhood. Results indicate that local governments’ spending decisions are significantly influenced by the actions of neighbouring municipalities. For total expenditures, there is evidence that a 10% increase in nearby municipalities’ expenditures boosts expenditures in a given municipality by around 3.8%.